Thyroid hormone activation by type2 deiodinase mediates exercise-induced peroxisome proliferator-activated receptor-gamma coactivator-1 alpha expression in skeletal muscle - Bocco, Barbara Miranda Leite da Costa [UNIFESP] (2019)
National Institute of Diabetes and Digestive and Kidney Diseases